Profil Keterampilan Pemecahan Masalah dan Motivasi Belajar Siswa pada Materi Fluida Statis - Tika Latipah; Rahmadhani Mulvia; Asep Irvan Irvani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Problem-solving skills are among the important competencies that students must have when learning physics in the 21st century. However, among static fluid materials, students are still found to have difficulty analyzing and solving physics problems, which is suspected to be related to students’ level of learning motivation. This study aims to describe the profiles of problem-solving skills and learning motivation among high school students in static fluid materials. The research method used is quantitative descriptive. The research subjects consisted of 46 students in grade XI of MIPA at a high school in Garut Regency. The research instruments included a problem-solving skills description test and a learning motivation questionnaire. The results showed that students' overall problem-solving skills were in the medium category with an average percentage of 55.9%. At the problem-solving stage, the understanding-of-the problem indicator had the highest percentage, at 71.1%. while the evaluation indicator had the lowest percentage at 41.1%. Student learning motivation is in the medium category with an average percentage of 59.32%. The results of this study show the need for learning efforts that are able to improve the ability to evaluate solutions and strengthen students' learning motivation in physics learning.